Pengaruh Service Excellence, Physical Environment, Dan Doctor – Patient Relationship Terhadap Revisit Intention Yang Dimediasi Oleh Patient Satisfaction Dalam Outpatient Department - Venny Venny; Veli Sungono (Jurnal Impresi Indonesia, 2025)
This study aims to determine what factors influence Revisit Intention and the role of Patient Satisfaction in mediating the relationship between variables. There are three independent variables and one moderating variable related to the Revisit Intention variable in the hospital. In accordance with this objective, the research method used in this study is a survey method with a cross-sectional approach. The unit of analysis in this study is patients who make repeat visits to the hospital. The data collection tool uses a questionnaire instrument whose data source comes from research respondents selected using the purposive sampling method. Cross-sectional data was taken from a private hospital in May 2025 which was obtained from 138 selected respondents. The results of the study from 138 respondents whose data had been processed showed that the doctor-patient relationship variable had a positive and significant influence on revisit intention mediated by patient satisfaction. Meanwhile, the hospital service excellence variable had no influence on revisit intention mediated by patient satisfaction. The physical environment variable had no influence on revisit intention mediated by patient satisfaction. The Doctor-Patient Relationship had the greatest positive influence on revisit intention. The results of this study are expected to provide suggestions to the Hospital to strengthen the factors that influence the interest of patients to revisit the outpatient clinic.